Absence of dentate nucleus resting‐state functional connectivity changes in nonneurological patients with gadolinium‐related hyperintensity on T1‐weighted images. Issue 2 (25th January 2019) - Mallio, Carlo A.; Piervincenzi, Claudia; Gianolio, Eliana; Cirimele, Vincenzo; Papparella, Luigi G.; Marano, Massimo; Quintiliani, Livia; Aime, Silvio; Carducci, Filippo; Parizel, Paul M.; Quattrocchi, Carlo C.
Abstract : Background: The dentate nuclei of the cerebellum are the areas where gadolinium predominantly accumulates. It is not yet known whether gadolinium deposition affects brain functions. Purpose/Hypothesis: To assess whether gadolinium‐dependent high signal intensity of the cerebellum on T1 ‐weighted images of nonneurological adult patients with Crohn's disease is associated with modifications of resting‐state functional connectivity (RSFC) of the cerebellum and dentate nucleus. Study Type: Observational, cross‐sectional. Population: Fifteen patients affected by Crohn's disease were compared with 16 healthy age‐ and gender‐matched control subjects. All participants underwent neurological, neurocognitive‐psychological assessment, and blood sampling. Field Strength/Sequence: 1.5‐T magnet blood oxygenation level‐dependent (BOLD) functional MRI. Assessment: High signal intensity on T1 ‐weighted images, cerebellum functional connectivity, neurocognitive performance, and blood circulating gadolinium levels. Statistical Tests: An unpaired two‐sample t ‐test (age and sex were nuisance variables) was used to investigate between‐group differences in cerebellar and dentate nucleus functional connectivity. Z‐statistical images were set using clusters determined by Z > 2.3 and a familywise error (FWE)‐corrected cluster significance threshold of P  = 0.05. Results: Dentate nuclei RSFC was not different ( P  = n.s.) between patients with gadolinium‐dependent high signal intensity on T1 ‐weighted images and controls. Pre‐ and postcentral gyrus bilaterally and the right supplementary motor cortex showed a decrease of RSFC with the cerebellum hemispheres ( P  < 0.05 FWE‐corrected) and was related to disease duration but not to gadodiamide cumulative doses ( P  = n.s.). Data Conclusion: Crohn's disease patients with gadolinium‐dependent hyperintense dentate nuclei on unenhanced T1 ‐weighted images do not show dentate nucleus RSFC changes. Level of Evidence : 2 Technical Efficacy Stage : 5 J. Magn. Reson. Imaging 2019;50:445–455.